(untitled) (Higher Education Politics and Economics, 2025)
Are state universities and state scholarship programs perpetuating income equality in the United States? Using data from Florida on the number of students from each public high school in the state who attended a State University System (SUS) university and the number who received a Florida Bright Futures (FBF) scholarship, this paper attempts to answer this question. The results of the models showed that an average high school with no disadvantaged students could expect to send 124 students to SUS universities and to have 121 students receive FBF scholarships, but the same average high school with 100% disadvantaged students could expect only seven students to go to SUS universities and seven students to receive FBF scholarships. The results indicate that the distribution of the benefits of state higher education funding and FBF scholarships is regressive.